PENGARUH LINGKUNGAN KERJA FISIK DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT LULU GROUP RETAIL REGIONAL OFFICE CAKUNG JAKARTA TIMUR - Dina Apriyani; Endang Kustini (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of Physical Work Environment and Work Motivation on Employee Performance at PT Lulu Group Retail Regional Office both partially and simultaneously. This research method uses a quantitative method with a descriptive approach. The sampling technique in this study used a non-probability sampling technique, namely a saturated sample with a total of 67 respondents. Data analysis using the SPSS version 23 program. The data analysis techniques used were: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression test, simultaneous correlation coefficient test, simultaneous determination coefficient test, T test and F test. Partial hypothesis testing of the Physical Work Environment variable (X1) obtained a calculated T value> T table (4.100> 1.997) and a significance value of 0.00 <0.05. This means that the Physical Work Environment (X1) has a significant effect on Employee Performance (Y). Partial hypothesis testing of the Work Motivation variable (X2) obtained a calculated T value > T table (5.269 > 1.997) and a significance value of 0.001 < 0.05. This means that Work Motivation (X2) has a significant effect on Employee Performance (Y). Simultaneous hypothesis testing obtained a calculated F value > F table (141.485 > 3.140) and a significance value of 0.000 < 0.05. It can be concluded that the Physical Work Environment (X1) and Work Motivation (X2) have a significant effect both simultaneously on Employee Performance (Y). The determination obtained Adjusted R square of 0.807, meaning that the variables of the Physical Work Environment and Work Motivation together have a contribution of 80.7% to Employee Performance. While the remaining 19.3% is influenced by other factors not examined in this study